Economic coercion and currency crises in target countries. (July 2015) - Peksen, Dursun; Son, Byunghwan
Despite significant research on the efficacy and inadvertent humanitarian and political effects of economic sanctions, surprisingly little is known about the possible economic and financial consequences of sanctions for target economies. Synthesizing insights from the currency crisis literature with sanctions scholarship, we argue that economic sanctions are likely to trigger currency collapses, a major form of financial crisis that impedes economic growth and prosperity. We assert that economic coercion instigates currency crises by weakening the economy and creating political risks conducive to speculative attacks by currency traders. To substantiate the theoretical claims, we use time-series cross-national data for the 1970–2005 period. The results from the data analysis lend support for the hypothesis that sanctions undermine the financial stability of target countries. The findings also indicate that the adverse effect of economic coercion on the financial stability of target economies is likely to be conditioned by the severity of the coercion and the type of actors involved in the implementation of sanctions. The findings of this article add to the sanctions literature demonstrating how economic coercion could be detrimental to the target economy beyond the immediate effect on trade and investment. It also complements and adds to the literature on political economy of currency crises that has so far overlooked the significant role that economic coercion plays in financial crises.